1996
DOI: 10.1002/j.1537-2197.1996.tb12700.x
|View full text |Cite
|
Sign up to set email alerts
|

Circumscription of Myrtales and their relationships to other rosids: evidence fromrbcL sequence data

Abstract: Despite intensive morphological and chemical studies on the Myrtales, the circumscription of the order remains poorly defined. To test the monophyly of Myrtales sensu Dahlgren and Thorne (Annals of the Missouri Botanical Garden 71: 633‐694, 1984), determine the relationships of some controversial families, and identify the most likely sister group of Myrtales, we conducted parsimony analyses on 80 rbcL sequences representing 36 taxa from families traditionally included in Myrtales and 44 taxa from other Rosida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(5 citation statements)
references
References 37 publications
0
2
0
2
Order By: Relevance
“…To determine whether multiple islands of most parsimonious trees were present (Maddison 1991), we conducted heuristic searches seeded with 1000 random addition sequences, using tree bisection and reconnection (TBR) with MULPARS on. Setting MULPARS on should facilitate the recovery of all trees within an island (Olmstead et al 1992(Olmstead et al , 1993Conti et al 1996). Two searches were conducted, using unweighted TABLE 3.…”
Section: Molecular Datamentioning
confidence: 99%
“…To determine whether multiple islands of most parsimonious trees were present (Maddison 1991), we conducted heuristic searches seeded with 1000 random addition sequences, using tree bisection and reconnection (TBR) with MULPARS on. Setting MULPARS on should facilitate the recovery of all trees within an island (Olmstead et al 1992(Olmstead et al , 1993Conti et al 1996). Two searches were conducted, using unweighted TABLE 3.…”
Section: Molecular Datamentioning
confidence: 99%
“…Subfamily Onagroideae are further divided into six tribes. Relationships among the seven subunits (including subfamily Ludwigioideae) have been somewhat stable since the first molecular phylogenies that sampled genera from multiple tribes (Conti et al, 1996), and the monophyly of most tribes has been confirmed in subsequent studies focused on the family (Levin et al, 2003(Levin et al, , 2004. Generic delimitations have changed considerably over the 2000s, particularly within the species-richest tribes Epilobieae Endlicher and Onagreae Dumortier, and eventually, leading to the re-establishment of tribe Gongylocarpeae J. Donnell Smith & Rose (Levin et al, 2003(Levin et al, , 2004Wagner et al, 2007).…”
mentioning
confidence: 99%
“…4), mas predominantemente Neotropical (seis dos Apesar de freqüentemente relacionada às Polygalaceae e Trigoniaceae nos sistemas tradicionais de classificação (e.g. CRONQUIST 1981;TAKHTAJAN 1997), estudos filogenéticos macromoleculares (CONTI et al 1996;CONTI et al 1997) posicionam Vochysiaceae na ordem Myrtales, como grupo-irmão de Myrtaceae. De fato, a associação das Vochysiaceae a esta ordem é evidenciada pela ocorrência conjunta de floema intraxilemático e de pontoações areoladas guarnecidas nos elementos de vaso, característica de Myrtales (METCALFE & CHALK 1950;JANSEN et al 2008), junto a outros caracteres anatômicos (QUIRK 1980;van VLIET & BAAS 1984;BAAS et al 2000) e embriológicos (TOBE & RAVEN 1983;BOESEWINKEL & VENTURELLI 1987)…”
Section: Serra Do Cipóunclassified